Evaluation Of Antipyretic Activity Using Cinnamomum Zeylanicum Aqueous Extract In Albino Wistar Rats (Journal of Pharmaceutical Negative Results, 2022)
The Cinnamomum zeylanicum derived components like cinnamaldehyde, or sodium cinnamate produces the hypothermic and antipyretic effects. Antipyretic activity is an activity in which the body temperature increases and that tends to the various kinds of problems and illnesses in the body. The antipyretic are the agents that help to reduce the extra body temperature which affects the creature. In our study we evaluated the antipyretic activity of Cinnamomum zeylanicum on Albino Wistar rats by extracting the Cinnamomum zeylanicum component using a Soxhlet apparatus and was freeze-dried to obtain crude water extract yield of 8.3% w/w. This freeze-dried extract was used in different dosage after making a stock solution of 40mg/ml in experimental albino Wistar rats and Swiss albino mice. The doses of aqueous extracts of Cinnamomum zeylanicum to be used in the study will be calculated based on previously documented LD50 on rats as per OECD guidelines (OECD_423). Through brewer’s yeast induced pyrexia method the total 36 Albino Wistar rats were procured for the study and divided into six groups, each group comprising six rats. It was seen that aqueous extract of Cinnamomum zeylanicum at the given dose of 400 mg/kg & 200mg/kg PO significantly (p<0.0001) reduced the rectal temperature of rats induced by brewer’s yeast injection at 60 minutes, 90 minutes, and 120 minutes. Therefore, in our study we found that the antipyretic effect of aqueous extract of both test drugs might be due to the inhibition of cyclo-oxygenase enzyme.